Mesothelin promoter variants are associated with increased soluble mesothelin-related peptide levels in asbestos-exposed individuals. Issue 6 (25th March 2017) - De Santi, Chiara; Pucci, Perla; Bonotti, Alessandra; Melaiu, Ombretta; Cipollini, Monica; Silvestri, Roberto; Vymetalkova, Veronika; Barone, Elisa; Paolicchi, Elisa; Corrado, Alda; Lepori, Irene; Dell'Anno, Irene; et al.
Abstract : Background: Soluble mesothelin-related peptide (SMRP) is a promising diagnostic biomarker for malignant pleural mesothelioma (MPM), but various confounders hinder its usefulness in surveillance programmes. We previously showed that a single nucleotide polymorphism (SNP) within the 3'untranslated region (3'UTR) of the mesothelin ( MSLN ) gene could affect the levels of SMRP. Objectives: To focus on SNPs located within MSLN promoter as possible critical genetic variables in determining SMRP levels. Methods: The association between SMRP and SNPs was tested in 689 non-MPM subjects and 70 patients with MPM. Reporter plasmids carrying the four most common haplotypes were compared in a dual luciferase assay, and in silico analyses were performed to investigate the putative biological role of the SNPs. Results: We found a strong association between serum SMRP and variant alleles of rs3764247, rs3764246 (in strong linkage disequilibrium with rs2235504) and rs2235503 in non-MPM subjects. Inclusion of the genotype information led to an increase in SMRP specificity from 79.9% to 85.5%. Although not statistically significant, the group with MPM showed the same trend of association. According to the in vitro luciferase study, rs3764247 itself had a functional role. In silico approaches showed that the binding sites for transcription factors such as Staf and ZNF143 could be affected by this SNP. The other SNPs were shown to interact with each other in a more complex way. Conclusions: These data support the suggestion that SMRP performance is affected by individual (ie, genetic) variables and that MSLN expression is influenced by SNPs located within the promoter regulatory region.